Catuspatha As A Landmark Of Semarapura City In Terms Of Physical And Socio-Cultural Aspects - Frysa Wiriantari; Syamsul Alam Paturusi; Ngakan Ketut Acwin Dwijendra; I Dewa Gede Agung Diasana Putra (International Journal of Engineering and Emerging Technology, 2020)
Abstract. The development of a city cannot be separated from how its people view a city. People who understand how the culture of the city will give a strong identity and character to the city. Over time, there are differences in how people perceive elements of the city, one of which is the catuspatha. Catuspatha is no longer interpreted as empty space but began to get additional functions as aesthetic and elemental elements of city landmarks (landmarks). There are several meanings arising from the physical aspects and socio-cultural aspects of a catuspatha as a landmark of the City of Semarapura. This research focuses on Catuspatha Semarapura City in terms of physical and socio-cultural aspects. The data search was carried out by means of litelature studies, field observations and interviews with people who were active in and around Semarapura City. By using a qualitative descriptive method, this research results that the Semarapura catuspatha in terms of physical size has different criteria with its environment so that it is physically prominent, unique, easy to remember, easily recognizable, has historical and aesthetic value. From the socio-cultural aspects of the area around the Semarapura catuspatha also functions as a node, in which at this location a variety of activities are held mainly related to social and cultural activities such as Tawur Kesanga, Ngulapin, Nebusin, Ngelawang, and other activities including Ogoh-ogoh parade activities, various festivals and folk parties and also cultural marches. Keyword: catuspatha, identity, landmarks, physical, social culture.